Lesson study-based mathematics instruction with a deep learning approach for enhancing elementary students’ mathematical literacy - Ahmad Yani T; Akbar Ramadhan; Hery Sutrisno; Dyan Hayuningtrisna Hadiwangsa; Dona Fitriawan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Mathematical literacy is a fundamental competency that enables students to apply mathematical knowledge in real-life situations. However, Indonesian students continue to demonstrate relatively low mathematical literacy performance, as indicated by the 2022 PISA results. Similar challenges are evident among elementary school students in Pontianak, who often experience difficulties in solving contextual mathematical problems. Aim: This study aimed to examine differences in mathematical literacy skills, determine the magnitude of the instructional effect, analyze the implementation process, and describe students’ mathematical literacy performance following lesson study-based mathematics instruction with a deep learning approach. Method: A mixed-methods approach with an embedded experimental design was employed. Quantitative data were collected through a quasi-experimental design involving 55 fourth-grade students in the experimental group and 65 students in the control group. Qualitative data were obtained through classroom observations and lesson study reflections. Data were analyzed using the Mann–Whitney U test and Cohen’s d effect size. Results: The findings revealed a significant difference in mathematical literacy skills between the experimental and control groups (p < .001). The intervention produced a Cohen’s d value of 0.3189, indicating a small-to-moderate practical effect. Qualitative findings showed that the lesson study cycle fostered a structured, collaborative, and reflective learning environment that enhanced students’ engagement and conceptual understanding. Conclusion: Lesson study-based mathematics instruction with a deep learning approach effectively enhances elementary students’ mathematical literacy by promoting contextual understanding, reflective learning, and meaningful application of mathematical concepts.